Connecting Hh, Dpp and EGF signalling in patterning of the Drosophila wing; the pivotal role of collier/knot in the AP organiser. - Crozatier, M.; Glise, B.; Vincent, A. (Development, 2002)
Hedgehog (Hh) signalling from posterior (P) to anterior (A) cells is the primary determinant of AP polarity in the limb field in insects and vertebrates. Hh acts in part by inducing expression of Decapentaplegic (Dpp), but how Hh and Dpp together pattern the central region of the Drosophila wing remains largely unknown. We have re-examined the role played by Collier (Col), a dose-dependent Hh target activated in cells along the AP boundary, the AP organiser in the imaginal wing disc. We found that col mutant wings are smaller than wild type and lack L4 vein, in addition to missing the L3-L4 intervein and mis-positioning of the anterior L3 vein. We link these phenotypes to col requirement for the local upregulation of both emc and N, two genes involved in the control of cell proliferation, the EGFR ligand Vein and the intervein determination gene blistered. We further show that attenuation of Dpp signalling in the AP organiser is also col dependent and, in conjunction with Vein upregulation, required for formation of L4 vein. A model recapitulating the molecular interplay between the Hh, Dpp and EGF signalling pathways in the wing AP organiser is presented.